SISTEM PENDUKUNG KEPUTUSANPEMILIHAN GURU TELADAN DENGAN SIMPLE ADDITIVE WEIGHTING METHOD (SAW) (STUDI KASUS DI SMA ANGKASA YOGYAKARTA) - Harliyus Agustian; Anton Setiawan Honggowibowo; Yuliani Indrianingsih (Compiler, 2012)
Decision Support System or DSS is a system that helps managers solve problems in a semi-structured. Many of the techniques used to make the DSS, onewith Fuzzy Logic Multi-Attribute Decision Making (MADM). Fuzzy logic  is oneproblem on feelings. Where the degree  of membership is usually representedwith a value of 0 and 1, with Fuzzy Logic is the degree of membership can be represented with a value between 0 and 1, which can be more balanced. High School Angkasa Yogyakarta is a place to educate students thus the students can be useful for Nation.In realizing, the need for good quality teachers who can become role models for students, so that teaching and  learning process will be better. Thus the need assessment conducted by the student or the principal to determine the ability of ateacher, both in the process of teaching or outside the teaching process. In the process of assessment needs to consider several factors than affect teacher performance. These factor related to teaching and learning process outside the process of theaching  anyothers  on the Indonesian Government Regulation Number 74 Year 2008 about the master of pedagogical,competence, personality, social and professional.High School Angkasa in conducting an assessment to each teacher based on the result of the vote.  So , to help assist in making selection for decision support of teacher to be made SPK. DSS will use fuzzy logic techniques that apply MADM SAW method in its calculation. It is expected that DSS can be an alternativein the selection of exeplary teacher in High School Yogyakarta.